THE PERFORMANCE OF SEVERAL LOCAL FEMALE CUCUMBER HYBRIDS UNDER DIFFERENT LEVELS OF WATER STRESS - S. S. Saeed; A. H. Hamad; S. M. Salih (مجلة الأنبار للعلوم الزراعية)
his experiment was conducted in an unheated plastic house in Al-Bu Shaaban on the outskirts of Ramadi during the 2024 season. It evaluated five locally produced hybrids, namely 2014, 2025, 2036, 2116, and 2000 designated B1, B2, B3, B4, and B5, respectively and compared them to the Kenz hybrid (B0) which is approved by the Horticulture Department of the Iraqi Ministry of Agriculture. The experiments were based on irrigation intervals of 3, 4, and 5 days (G1, G2, and G3, respectively) using the randomized complete block design (RCBD). The 8 traits measured were plant height, number of nodes per plant, leaf area per plant, plant yield, fruits per plant, early plant yield, dry weight of shoots, and leaf proline content. The B2 hybrid excelled at 43.911 nodes per plant-1, while the B3 excelled in leaf area and number of fruits, reaching 143.46 dm2 and 53.45 fruits per plant-1, respectively. The B4 and B5 hybrids excelled in plant yield at 4.66 and 4.65 kg plant-1, respectively, while the B0 excelled by giving the highest early yield of 1.91 kg plant-1. The dry weight of the shoot and plant height did not show any significant difference between the hybrid and the hybrid superiority (B5). The B5 recorded a leaf proline concentration of 235.00 mg L-1, while the comparison hybrid (B0) had the lowest at 206.55 mg L-1. As for irrigation level, it significantly exceeded the first level (G1) in the number of cuttings, leaf area, plant yield, number of fruits, dry weight of the shoot, and plant height, amounting to 45.47 plant nodes, 152.95 dm2, 4.99 kg of plant-1, 59.01 fruits per plant-1, 82.39 g of plant-1, 286.77 cm, respectively with the G3 significantly superior in early yield at 1.93 kg per plant-1